2020
DOI: 10.1111/fare.12483
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Parental Stress Scale With a Foster Carer Cohort

Abstract: Objective Using a cohort of foster and kin carers, the research examined the underlying factor structure of the Parental Stress Scale (PSS; Berry & Jones, 1995). A hypothesized underlying two‐dimensional theoretical model was explored. Background With the growing demands on the foster care system, including poor retention and recruitment of foster carers, there is an urgent need to explore the positive and negative factors that may influence carers continued engagement in the role. Method The factor structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…The CFA shows that the Spanish scale retains the structure determined in the EFA by the authors who validated it in 2007, and the fit indices that were obtained in this study are adequate. Although the original scale that was developed by Berry and Jones [ 2 ] consists of four factors (“Parental Stressors”, “Lack of Control”, “Parental Satisfaction”, and “Parental Rewards”), internationally there is inconsistency between the factors that were obtained in the process of adapting the instrument, with two main factors (“Parental Satisfaction” and “Parental Stressors”) being commonly identified [ 34 , 35 , 36 ]. Only three studies were found in which the original tetra-factorial structure was confirmed with good statistical fit [ 34 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFA shows that the Spanish scale retains the structure determined in the EFA by the authors who validated it in 2007, and the fit indices that were obtained in this study are adequate. Although the original scale that was developed by Berry and Jones [ 2 ] consists of four factors (“Parental Stressors”, “Lack of Control”, “Parental Satisfaction”, and “Parental Rewards”), internationally there is inconsistency between the factors that were obtained in the process of adapting the instrument, with two main factors (“Parental Satisfaction” and “Parental Stressors”) being commonly identified [ 34 , 35 , 36 ]. Only three studies were found in which the original tetra-factorial structure was confirmed with good statistical fit [ 34 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies were found in which the original tetra-factorial structure was confirmed with good statistical fit [ 34 , 37 , 38 ]. This factorial inconsistency could be explained by Pontoppidan et al [ 39 ] and Harding et al [ 35 ], who argue that the tetra-factorial model appears to be a subdivision of two primary factors, whereby the “Parental Stressors” and “Lack of Control” factors make up the “Parental Stressors” factor, while the “Parental Satisfaction” and “Parental Rewards” factors make up the “Parental Satisfaction” factor. An analysis of the scientific literature suggests that the different settings and populations in which the scale has been validated affect the stability of the items and the presence of the different factors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the validity and reliability of the PSS tool indicate good internal consistency (Algarvio et (Berry & Jones, 1995) and convergent validity was reported between PSS scores and parental anxiety and family functioning (Zelman & Ferro, 2018). Whereas a positive concurrent validity was reported between PSS and perceived stress scale and parenting stress index (Berry & Jones, 1995;Harding et al, 2020).…”
Section: Outcomementioning
confidence: 98%
“…Studies on the validity and reliability of PSS tools indicate good internal consistency, construct validity, convergent validity, and test-retest reliability [29][30][31][32][33][34]. Notably, Cronbach's alpha coe cient for the internal consistency of the items in the Parental Stress Scale was 0.79.…”
Section: Parental Stress Score Outcome Measurementioning
confidence: 99%